Bacterial cellulose-based conductive flexible material as well as preparation method and application thereof

By plating metal conductive coating on the surface of the bacterial cellulose film, the problem that existing materials are difficult to take into account multiple properties is solved, and a conductive bacterial cellulose film with excellent conductive properties and environmentally friendly is prepared, suitable for intelligent wearable sensing Device.

CN119410017AActive Publication Date: 2025-02-11NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411556646.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing conductive flexible matrix materials are difficult to take into account the conductive properties, mechanical strength, washability, structural stability and environmentally friendly. Bacterial cellulose is not conductive and cannot be directly applied to wearable sensing devices.

Method used

Biocopolymerization in situ modification combined with polymer-assisted metal deposition technology is used to coat the surface of the bacterial cellulose film with copper, nickel, gold or silver to prepare a conductive bacterial cellulose film. The method includes three steps: surface amine modification, polymer brush chemical modification and metal conductive coating growth.

Benefits of technology

The preparation of conductive bacterial cellulose film is realized, with excellent conductivity, good mechanical strength and environmental friendliness, and is suitable for intelligent wearable sensing devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410017A_ABST
    Figure CN119410017A_ABST
Patent Text Reader

Abstract

The invention discloses a bacterial cellulose-based conductive flexible material as well as a preparation method and application thereof, and belongs to the technical field of intelligent wearable flexible electronic sensing. Amino-modified bacterial cellulose is obtained by adopting a biocopolymerization in-situ modification technology, then a metal conductive coating is constructed on the surface of the amino-modified bacterial cellulose membrane by adopting a polymer-assisted metal deposition technology, so that the conductive bacterial cellulose membrane is prepared, and a conductive bacterial cellulose membrane-based friction nano-generator principle is further utilized, so that the conductive bacterial cellulose membrane-based friction nano-generator is obtained. The flexible electronic intelligent wearable sensor has the advantages of being simple in structure, low in cost and environment-friendly, achieving sensitive output of electric signals and charging of LED lamps and stopwatch small-power equipment, being applied to wearable sensing devices and monitoring human body motion states such as walking and running, and having wide prospects in the field of preparing novel flexible electronic intelligent wearable sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible sensing materials, and in particular relates to a conductive flexible matrix material of a bacterial cellulose-based intelligent wearable sensing device, and a preparation method and application thereof. Background Art

[0002] Smart wearable sensing devices are flexible electronic devices that can be "worn" on the body and used during physical activities. Smart wearable sensing devices have the advantages of intelligent management, portability, and convenient use and operation. Wearable electronic devices can almost be integrated with the human body and can be widely used in health monitoring, wearable biosensors, human-computer interaction and other fields, which may bring disruptive changes to human cognition and life in the future. At present, various conductive flexible matrix materials used to manufacture smart wearable sensors have been widely studied, including metal materials, carbon-based fiber materials and polymer composites. However, it is difficult for existing materials to take into account the common advantages of conductivity, mechanical strength, washability, structural stability and environmental friendliness.

[0003] Bacterial cellulose is composed of glucose units connected by β-1,4-glycosidic bonds. It has many advantages such as high purity, high crystallinity, high air permeability, high specific surface area, excellent mechanical properties, excellent biocompatibility and biodegradability, and is an environmentally friendly new bio-nanomaterial, which makes it uniquely advantageous as a substrate for wearable smart fabrics. However, natural bacterial cellulose is not conductive and cannot meet the conductivity requirements of the substrate for wearable sensing devices and be directly used.

[0004] At present, the preparation methods of conductive bacterial cellulose membrane mainly include in-situ modification, post-functionalization modification and co-regeneration, by introducing conductive materials such as nano-metal particles, carbon nanofibers and polymer composite materials. Won-Il Park [1] et al. used an in-situ modification method to culture bacterial cellulose in HS medium dispersed with multi-walled carbon nanotubes to prepare BC / MWCNT composite materials. However, the conductive nanofiller is prone to sedimentation in the static fermentation system of bacterial cellulose, resulting in uneven distribution in the modified functional material, and the blending modification process often destroys the crystalline structure and excellent mechanical properties of the bacterial cellulose. Wei Shao et al. [2] BC / GE composite membranes were prepared by introducing graphene nanosheets into the BC matrix through post-functional modification using a simple blending method. However, the nanofillers adsorbed on the surface are easy to fall off, and the exact amount of adsorption on the surface of the material and the uniform distribution of molecules are difficult to effectively control, resulting in unsatisfactory conductive properties. Qianqian Liang [3]et al. prepared BC / CNT spiral fibers with significant mechanical properties by using BC as a water-sensitive matrix and CNT as an active sensing material, blending the two and using dry-wet spinning and winding processes. However, bacterial cellulose is difficult to dissolve due to its high crystallinity, and the viscosity of the solution is too high. Its thermal stability and non-volatility make it unsuitable for electrospinning. In addition, the mixing effect of conductive fillers and bacterial cellulose solutions is poor, and it is difficult to achieve molecular-level mixing.

[0005] 【1】Carbohydrate Polymers,2009,77,457–463

[0006] 【2】Carbohydrate Polymers,2016,138,166-171

[0007] 【3】ACS Applied Materials & Interfaces, 2022 14, 21319-21329. Summary of the invention

[0008] The purpose of the present invention is to provide a bacterial cellulose-based conductive flexible material and a preparation method and application thereof, taking into account the common advantages of conductive properties, mechanical strength, washability, structural stability and environmental friendliness.

[0009] The technical solution adopted by the present invention is:

[0010] The metal (copper, nickel, gold, silver, etc.) is plated on the surface of bacterial cellulose membrane by biopolymerization in-situ modification combined with polymer-assisted metal deposition technology to obtain conductive bacterial cellulose membrane, which is used as the base material to construct smart wearable sensor devices. The preparation method is divided into three steps:

[0011] Firstly, the surface amino-modified bacterial cellulose membrane was prepared by bio-copolymerization in-situ modification technology;

[0012] Then, the surface of amino-modified bacterial cellulose membrane was chemically modified by grafting polymer brushes through surface-initiated atom transfer radical polymerization, and a polymer brush containing functional groups capable of pairing with heteroionic ions, polymethacryloyloxyethyltrimethylammonium chloride (PMETAC), was introduced.

[0013] Then induce the electroless deposition of active ion catalyst [PdCl4] 2- Ion exchange and pairing are carried out, and finally the conductive coatings of metal Cu, Ni, Ag, and Au are assisted to grow controllably on the surface of bacterial nanocellulose, thereby finally preparing a conductive bacterial cellulose membrane.

[0014] The invention discloses a bacterial cellulose-based conductive flexible material, wherein the conductive material is a bacterial cellulose film with a metal Cu, Ni, Ag or Au coating loaded on the surface.

[0015] The bacterial cellulose membrane is a bacterial cellulose membrane with surface amine groups modified.

[0016] The conductive material is a porous nanofiber structure. Bacterial cellulose, as a natural biomaterial, has a nanofiber network structure with a high specific surface area, excellent mechanical properties and complete biodegradability. However, due to the strong hydrogen bonding within and between bacterial cellulose molecules, its solubility in conventional organic solvents is very low. Therefore, the first step of preparing conductive bacterial cellulose by polymer-assisted metal deposition technology is limited, that is, the amount of grafting initiator on the surface of bacterial cellulose membrane through post-functionalization modification is very low and the density distribution is uncontrollable, which makes the amount of grafted modified polymer on the membrane surface initiated by atom transfer radical polymerization also very low and the density distribution is uncontrollable, thereby hindering the subsequent second step of catalyst molecule fixation process with active ions that can induce electroless deposition to exchange and pair, and ultimately affecting the controllable growth of assisting metal in electroless deposition on the surface of bacterial cellulose membrane in the third step.

[0017] The present invention introduces a metal conductive coating on the surface of an amine-modified bacterial nanocellulose membrane through a polymer-assisted metal deposition technology to obtain a conductive bacterial cellulose membrane.

[0018] The preparation method of the conductive bacterial nanocellulose film comprises the following process steps:

[0019] (1) Immobilizing the initiator on the surface of bacterial cellulose: preparing a reaction solution for initiating atom transfer radical polymerization on the surface of bacterial cellulose membrane, immersing the bacterial cellulose membrane in the solution for reaction, taking it out and repeatedly washing it with deionized water, and finally freeze-drying it in a vacuum to obtain a bacterial cellulose membrane with the initiator immobilized on the membrane surface.

[0020] (2) Introduction of polymer brushes by atom transfer radical polymerization on the surface of bacterial cellulose membrane: The reaction solution required for the modification of bacterial cellulose membrane with surface polymer brushes was prepared, and the bacterial cellulose membrane was immersed in the solution for reaction, taken out and repeatedly washed with deionized water, and finally freeze-vacuum dried to obtain a bacterial cellulose membrane with a polymer brush on the surface that can pair with heteroionic functional groups - poly(methacryloyloxyethyltrimethylammonium chloride) (PMETAC).

[0021] (3) Growth of metal (Cu, Ni, Ag, Au, etc.) conductive coating: Prepare active ion solution for electroless deposition and copper layer plating bath reaction solution, immerse the bacterial cellulose membrane modified by surface polymer brush into the active ion solution, carry out ion exchange and pairing reaction, and then convert [PdCl4] 2- The paired bacterial cellulose membranes are placed in a copper layer plating bath reaction solution for static deposition, taken out and repeatedly washed with deionized water, and finally freeze-dried in a vacuum to obtain a conductive bacterial cellulose membrane.

[0022] Wherein, in step (1), the solution is a uniformly mixed solution of dichloromethane, triethylamine, and 2-bromoisobutyryl bromide in a volume ratio of 100-50:0.5-5:0.5-2;

[0023] Wherein, in step (2), the solution is a uniformly mixed solution of bipyridine, methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, methanol (MEOH), cuprous chloride (CuCl) and cupric bromide (CuBr2) in a molar ratio of 20 to 1: 5000 to 100: 4000 to 100: 10 to 1: 10 to 0.1;

[0024] Wherein, in steps (1) and (2), the reaction system needs to be carried out under the protection of an inert gas. Preferably, the inert gas is N2, and the inert gas protection time is 5-10 min.

[0025] Wherein, in step (2), the reaction temperature is 20°C-30°C, and the reaction time is 0.5-4h.

[0026] Wherein, in step (3), the molar concentration of the active ion solution for electroless deposition is 0.01-0.1 mM (NH4)2PdCl4 solution, and more preferably the molar concentration is 0.05 mM (NH4)2PdCl4 solution;

[0027] In step (3), the reaction time is 15-120 min;

[0028] Wherein, in step (3), the metal plating bath reaction solution is a mixed solution of NaOH, CuSO4 or AgNO3 or HAuCl4 or NiSO4, KNaC4H4O6 and formaldehyde, and the static electroless deposition reaction time is 50-60 minutes;

[0029] The molar concentration of NaOH is 1-10 mol / L, the molar concentration of CuSO4 or AgNO3 or HAuCl4 or NiSO4 is 1-10 mol / L, the molar concentration of KNaC4H4O6 is 1-10 mol / L, the molar concentration of formaldehyde is 1-10 mol / L, and the mass ratio of the mixed solution of NaOH, CuSO4 or AgNO3 or HAuCl4 or NiSO4 and KNaC4H4O6 is: 10-1:10-1:10-1;

[0030] The temperature of freeze-vacuum drying of the amino bacterial cellulose membrane is -50°C to -60°C, and the drying time is 4-5h.

[0031] The bacterial cellulose membrane is an amine-modified bacterial cellulose membrane.

[0032] The method for preparing a microbial copolymerized conductive bacterial cellulose film of the present invention comprises the following steps:

[0033] Step 1), synthesizing an amine-modified bacterial cellulose membrane through microbial copolymerization;

[0034] Step 2), metal Cu, Ni, Ag, Au are plated on the surface of bacterial cellulose membrane by polymer-assisted metal deposition technology to obtain conductive bacterial cellulose membrane.

[0035] The method for synthesizing amino-modified bacterial cellulose membrane by microbial copolymerization is as follows:

[0036] The microorganisms are inoculated into a fermentation medium and statically cultured at 28 to 32° C. for 3 to 7 days to obtain a bacterial cellulose membrane with surface amino groups modified.

[0037] In the fermentation medium, glucosamine and glucose are mixed in a molar ratio of 0-100:0-100, and amine-modified bacterial cellulose with different amine group densities is biosynthesized by microorganisms.

[0038] Preferably, in the fermentation medium, glucosamine and glucose are mixed at a molar ratio of 25-100:25-100; more preferably, glucosamine and glucose are mixed at a molar ratio of 75:25.

[0039] The microorganism is a strain capable of producing bacterial cellulose film; preferably, the strain is Komagataeibacter xylinus ATCC23770 (American Type Culture Collection).

[0040] Among them, when the strain used to produce bacterial cellulose film is Acetobacter xylinum, the culture medium is HS culture medium, and its formula is: 20g / L glucose (sterilized separately), 5g / L yeast extract, 5g / L peptone, 1.2g / L citric acid monohydrate and 2.7g / L disodium hydrogen phosphate, sterilized at 115°C for 20min.

[0041] The strain for producing amino bacterial cellulose film is Acetobacter xylinum, and the culture condition is 30° C. and the culture time is 5-7 days.

[0042] Glucosamine is used as a functional carbon source and added to the HS culture medium together with glucose carbon source, and different feed ratios of the two are adjusted, and the molar ratio of glucosamine to glucose is 0.01 to 1:1, and amine-modified bacterial cellulose with different amine group densities is biosynthesized by microbial catalysis. Further preferably, glucosamine and glucose are mixed in a molar ratio of 0:100, 25:75, 50:50, 75:25, and 100:0.

[0043] The amine group density of the amine-modified bacterial cellulose ranges from 0 to 350 μmol / g.

[0044] The preparation method of the conductive bacterial nanocellulose membrane prepared by the above preparation method is also within the protection scope of the present invention.

[0045] The application of the above-mentioned conductive bacterial cellulose film in the intelligent wearable sensor device is also within the protection scope of the present invention.

[0046] The conductive bacterial cellulose membrane of the present invention is firstly synthesized into an amino bacterial cellulose membrane by microbial copolymerization, and then metals Cu, Ni, Ag and Au are plated on the surface of the bacterial cellulose membrane by polymer-assisted metal deposition technology to prepare a conductive bacterial nanocellulose membrane.

[0047] The conductive bacterial cellulose membrane obtained by the present invention is a 3D nano-net structure. By adjusting the surface amino group density of the amino bacterial cellulose membrane of the base material, the time of the surface polymer brush initiating graft polymerization, etc., a conductive bacterial cellulose membrane with adjustable surface metal Cu, Ni, Ag, Au coating coating amount is obtained, and its conductive performance can be improved. The coating amount of the metal Cu, Ni, Ag, Au conductive coating varies in the range of 0 to 20 mmol / g with the surface amino group density of the bacterial cellulose membrane; the coating amount of the metal Cu, Ni, Ag, Au conductive coating varies in the range of 0 to 100 mmol / g with the polymer graft polymerization time.

[0048] Conductive bacterial cellulose film and polytetrafluoroethylene film form a friction nanogenerator that can power small devices such as LEDs and stopwatches.

[0049] The present invention provides an application of the conductive bacterial cellulose membrane material in an intelligent wearable sensor device.

[0050] Furthermore, the conductive bacterial cellulose prepared by the present invention is used in intelligent wearable sensor devices. The production process is green and environmentally friendly and can be produced on a large scale. Its air permeability and biocompatibility can be well attached to human skin, thereby realizing the monitoring of the body's movement status.

[0051] The conductive bacterial cellulose in the present invention is prepared by biological in-situ copolymerization, surface-initiated atom transfer radical polymerization and polymer-assisted metal deposition. Glucosamine and ordinary glucose carbon source are biopolymerized together to form an amine-modified bacterial cellulose nanofiber membrane by utilizing microbial metabolic synthesis, and a polymer brush containing a pairing heteroionic functional group is further introduced on the fiber membrane surface by surface-initiated atom transfer radical polymerization technology, and then a metal conductive coating is introduced on the bacterial nanocellulose membrane surface based on polymer-assisted metal deposition technology. By adjusting the amine group density and the polymer brush modification time, the density and height of the copper layer can be adjusted to improve the conductive performance of the conductive bacterial cellulose membrane.

[0052] Polymer-assisted metal deposition technology is a method that induces and assists the electroless deposition of metals by grafting a polymer molecular layer on the surface of a substrate. This technology can prepare metal coating films with high adhesion / high flexibility / high conductivity / high smoothness on the inner / outer surfaces of various flexible / rigid substrates in a solution state. It can effectively solve the limitations of conventional metal film growth technologies such as vacuum coating or nanoprinting in terms of preparation cost / film quality / substrate morphology, and is compatible with a variety of printing technologies to prepare specific metal patterns. Therefore, it has great application prospects in the preparation of flexible conductor materials and flexible devices.

[0053] The present invention proposes a method for preparing conductive bacterial cellulose nanofiber membrane through in-situ modification of biopolymerization combined with polymer-assisted metal deposition technology, and constructs a biodegradable, stable and efficient friction nanogenerator (TENG) based on the conductive bacterial cellulose nanofiber membrane, thereby realizing the application of conductive bacterial cellulose nanofiber membrane-based TENG in smart wearable sensing devices.

[0054] Beneficial effects: Compared with the prior art, the present invention has the following effects: (1) The conductive bacterial cellulose membrane of the present invention is plated with metal on the membrane surface, so that it has excellent conductive properties; the raw materials used are biocompatible and biodegradable substances; in addition, the membrane material has the characteristics of wear resistance, reusability, foldability and bendability; (2) The preparation method of the present invention is simple, low-cost and green. (3) The conductive material of the present invention has good application prospects in the field of smart wearable sensor devices, and is of great significance to environmental protection, energy utilization, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0056] Figure 1 This is a macroscopic image of the amino bacterial cellulose membrane;

[0057] Figure 2 This is a macroscopic image of the conductive bacterial cellulose film;

[0058] Figure 3 The graph is a graph showing the change in mechanical properties of amine-based membranes with different densities;

[0059] Figure 4 The surface resistance data of the conductive bacterial cellulose membrane with different amine group densities before and after copper plating;

[0060] Figure 5 The data diagram of the triboelectric performance of the conductive bacterial cellulose-based friction nanogenerator obtained by the bacterial cellulose membrane with different amine group density at different polymer grafting modification time;

[0061] Figure 6 The graph is a graph showing the change in mechanical properties during the modification process of amine-based membranes with different densities;

[0062] Figure 7 This is the infrared chromatographic analysis diagram of amino bacterial cellulose membrane and its modification process;

[0063] Figure 8 Scanning electron micrograph of the conductive bacterial cellulose prepared in Example 4;

[0064] Fig. 9 Figure 1: Conductive bacterial cellulose-based triboelectric nanogenerators powering small devices such as LEDs and stopwatches;

[0065] Fig.10 This is a diagram of the degradation process of the amino-based film and the copper-plated film. DETAILED DESCRIPTION

[0066] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0067] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0068] Example 1

[0069] In the following embodiment, a method for preparing a conductive bacterial cellulose film comprises the following steps:

[0070] (1) Preparation of amine-modified bacterial cellulose

[0071] Komagataeibacter xylinus ATCC 23770 (American Type Culture Collection) was used as the strain, and glucosamine was added into HS culture medium together with glucose as a functional carbon source. Different feed ratios of the two were adjusted (the molar ratios were 0:100, 25:75, 50:50, 75:25, and 100:0, respectively). The two were cultured at 30°C for 6 days through a microbial catalytic biosynthetic metabolic pathway, and directly biopolymerized to synthesize amino-modified bacterial cellulose with different amine group densities. The amino-modified bacterial cellulose membrane was taken out and placed in a NaOH solution, treated at a water bath temperature of 80-90°C for 3 hours, then taken out, and rinsed with deionized water until neutral to obtain the amino-modified bacterial cellulose membrane.

[0072] The HS culture medium used for Acetobacter xylinum is composed of 20 g / L glucose (sterilized separately), 5 g / L yeast extract, 5 g / L peptone, 1.2 g / L citric acid monohydrate and 2.7 g / L Na2HPO4, sterilized at 115°C for 20 min.

[0073] Table 1 Carbon source ratio

[0074]

[0075] (2) The initiator is fixed on the surface of amino bacterial cellulose:

[0076] The amino-modified bacterial cellulose was placed in a beaker, and 50 mL of dichloromethane, 0.83 mL of triethylamine, and 0.67 mL of 2-bromoisobutyryl bromide were added to the container in sequence under N2 protection, and the mixture was gently shaken and mixed for a uniform reaction. The reaction time was 10 min. After the reaction was completed, the material was taken out and washed with dichloromethane, ethanol, and deionized water in sequence, and freeze-dried and stored in a desiccator.

[0077] (3) Introduction of surface polymer brushes:

[0078] The bacterial cellulose substrate with the fixed initiator was placed in a Shrek bottle, and 292.8 mg of bipyridine, 12 mL of methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, 12 mL of methanol (MEOH), 66 mg of cuprous chloride (CuCl) and 43.2 mg of cupric bromide (CuBr2) were added to the bottle in sequence; the Shrek bottle was immersed in a 25°C water bath and N2 was passed for 5 minutes, and magnetic stirring was performed until the monomer was completely dissolved. After reacting for 2 hours, the material was taken out and washed with clean water several times, and freeze-dried and freeze-dried, and stored in a desiccator.

[0079] (4) Growth of Cu conductive coating:

[0080] Prepare 0.05mmol / L (NH4)2PdCl4 solution, put the bacterial cellulose membrane modified by surface poly(methacryloyloxyethyltrimethylammonium chloride) (PMETAC) brush into ammonium chloropalladate solution, and carry out ion exchange and pairing reaction for 1h, thereby converting [PdCl4] 2- The paired bacterial cellulose membranes were placed in a mixed solution of 1.4 g NaOH, 1.6 g CuSO4, 1.4 g KNaC4H4O6, 1.5 mL formaldehyde and 100 mL deionized water for static deposition for 1 hour, and then freeze-dried at a freeze-drying temperature of -50°C for 4 hours and stored in a desiccator.

[0081] like Figure 1 Shown is a macroscopic photograph of an amino-density bacterial cellulose film.

[0082] like Figure 2Shown is a macroscopic photograph of a conductive bacterial cellulose membrane.

[0083] like Figure 3 The figure shows the change of mechanical properties of surface amino-modified bacterial cellulose membranes obtained with different feeding ratios of glucose to glucosamine. As the ratio of amino groups increases, the tensile strength of amino-modified bacterial cellulose membranes decreases.

[0084] like Figure 4 Shown is the surface resistance data of the surface amino-modified bacterial cellulose membrane before and after copper plating obtained with different glucose to glucosamine feed ratios.

[0085] The results show that after treatment with polymer-assisted metal deposition technology, the surface resistance of the bacterial cellulose membrane is greatly reduced, and the membrane surface can achieve conductive effect, further proving the successful construction of the copper plating coating.

[0086] Example 2

[0087] In the following embodiments, the amino bacterial cellulose membrane synthesized by biological in situ copolymerization is used as the base material, and the conductive bacterial cellulose is synthesized by polymer-assisted metal deposition technology, and its preparation method is as follows:

[0088] (1) Preparation of amino bacterial cellulose:

[0089] Komagataeibacter xylinus ATCC 23770 (American Type Culture Collection) was used as the strain, and glucosamine was added into HS culture medium together with glucose as a functional carbon source. Different feed ratios of the two were adjusted (the molar ratios were 0:100, 25:75, 50:50, 75:25, and 100:0, respectively). The two were cultured at 30°C for 6 days through a microbial catalytic biosynthetic metabolic pathway, and directly biopolymerized to synthesize amino-modified bacterial cellulose with different amine group densities. The amino-modified bacterial cellulose membrane was taken out and placed in a NaOH solution, treated at a water bath temperature of 80-90°C for 3 hours, taken out, and rinsed with deionized water until neutral to obtain the amino-modified bacterial cellulose membrane.

[0090] The HS medium used for Acetobacter xylinum is composed of 20 g / L glucose (sterilized separately), 5 g / L yeast extract, 5 g / L peptone, 1.2 g / L citric acid monohydrate and 2.7 g / L Na2HPO4, sterilized at 115°C for 20 min. (2) Initiator fixed on the surface of amino bacterial cellulose:

[0091] The amino-modified bacterial cellulose was placed in a beaker, and 50 mL of dichloromethane, 0.83 mL of triethylamine, and 0.67 mL of 2-bromoisobutyryl bromide were added to the container in sequence under N2 protection, and the mixture was gently shaken and mixed for a uniform reaction. The reaction time was 10 min. After the reaction was completed, the material was taken out and washed with dichloromethane, ethanol, and deionized water in sequence, and freeze-dried and stored in a desiccator.

[0092] (3) Introduction of surface polymer brushes:

[0093] Place the bacterial cellulose substrate with the fixed initiator in a Shrek bottle, and add 292.8 mg of bipyridine, 12 mL of methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, 12 mL of methanol (MEOH), 66 mg of cuprous chloride (CuCl) and 43.2 mg of cupric bromide (CuBr2) to the bottle in sequence. Immerse the Shrek bottle in a 25°C water bath and pass N2 protection for 5 minutes, and stir magnetically until the monomer is completely dissolved. After reacting for 0.5, 2 hours, and 4 hours respectively, take out the material, wash it with deionized water several times, freeze-dry it, and store it in a desiccator.

[0094] (4) Growth of Cu conductive coating:

[0095] Prepare 0.05mmol / L (NH4)2PdCl4 solution, put the bacterial cellulose membrane modified by surface poly(methacryloyloxyethyltrimethylammonium chloride) (PMETAC) brush into ammonium chloropalladate solution, and carry out ion exchange and pairing reaction for 1h, thereby converting [PdCl4] 2- The paired bacterial cellulose membranes were placed in a mixed solution of 1.4 g NaOH, 1.6 g CuSO4, 1.4 g KNaC4H4O6, 1.5 mL formaldehyde and 100 mL deionized water for static deposition for 1 hour, and then freeze-dried at a freeze-drying temperature of -50°C for 4 hours and stored in a desiccator.

[0096] like Figure 5 The figure shows the conductive bacterial cellulose membrane prepared in Example 2, which is combined with a polytetrafluoroethylene membrane to form a friction nanogenerator to test its friction nano properties. Figure 5The three independent figures in the figure respectively represent that the polymer brush grafting time is 0.5h (leftmost figure), the polymer brush grafting time is 2h (middle figure), and the polymer brush grafting time is 4h (rightmost figure); 1, 2, 3, 4, and 5 in each figure respectively represent the blank bacterial cellulose membrane, the amine-modified bacterial cellulose membrane obtained when the feed ratio of glucosamine to glucose is 25:75, the amine-modified bacterial cellulose membrane obtained when the feed ratio of glucosamine to glucose is 50:50, the amine-modified bacterial cellulose membrane obtained when the feed ratio of glucosamine to glucose is 75:25, and the amine-modified bacterial cellulose membrane obtained when the feed ratio of glucosamine to glucose is 100:0. The results show that when there are no amine groups on the membrane surface, there is basically no triboelectric effect, but at the same amine group density, as the polymer brush modification grafting time increases, the amount of electricity generated by surface friction also increases.

[0097] Example 3

[0098] In the following embodiments, the amino bacterial cellulose membrane synthesized by biological in situ copolymerization is used as the base material, and the conductive bacterial cellulose is synthesized by polymer-assisted metal deposition technology, and its preparation method is as follows:

[0099] (1) Preparation of bacterial cellulose with different amine group densities:

[0100] Glucosamine was used as a functional carbon source and glucose carbon source in molar ratios of 0:100, 25:75, 50:50, 75:25, and 100:0, respectively, and the two were directly biopolymerized to synthesize amino-modified bacterial cellulose with the same amine group density through microbial catalytic biosynthesis metabolic pathway and cultured at 30°C for 5 days. The amino-modified bacterial cellulose membrane was taken out and placed in a NaOH solution, treated at 80°C for 2-4 hours, then taken out, rinsed with deionized water until neutral, and freeze-dried to obtain the amino-modified bacterial cellulose membrane.

[0101] (2) The initiator is fixed on the surface of amino bacterial cellulose:

[0102] The amino-modified bacterial cellulose was placed in a beaker, and 50 mL of dichloromethane, 0.83 mL of triethylamine, and 0.67 mL of 2-bromoisobutyryl bromide were added to the container in sequence under N2 protection, and the mixture was gently shaken and mixed for a uniform reaction. The reaction time was 10 min. After the reaction was completed, the material was taken out and washed with dichloromethane, ethanol, and deionized water in sequence, and freeze-dried and stored in a desiccator.

[0103] (3) Introduction of surface polymer brushes:

[0104] The bacterial cellulose substrate with the fixed initiator was placed in a Shrek bottle, and 292.8 mg of bipyridine, 12 mL of methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, 12 mL of methanol (MEOH), 66 mg of cuprous chloride (CuCl) and 43.2 mg of copper bromide (CuBr2) were added to the bottle in sequence. The Shrek bottle was immersed in a 25°C water bath and N2 was passed for 5 minutes, and magnetic stirring was performed until the monomer was completely dissolved. After reacting for 4 hours, the material was taken out and washed with deionized water several times, and freeze-dried and freeze-dried, and stored in a desiccator.

[0105] (4) Growth of Cu conductive coating:

[0106] See Example 1.

[0107] like Figure 6 The figure shows the change in mechanical properties of the conductive bacterial cellulose membrane obtained by bio-copolymerization at different feed ratios of glucosamine to glucose after polymer-assisted metal deposition modification (1, 2, 3, 4, 5 correspond to the ratios of 0:100, 25:75, 50:50, 75:25, 100:0, respectively). The results show that when the feed ratio of glucosamine to glucose changes at 0:100, 25:75, 50:50, 75:25, as the ratio of glucosamine increases, the tensile strength of the conductive bacterial cellulose membrane first decreases slightly, and then increases slightly. When the feed ratio of glucosamine to glucose is 75:25, the tensile strength of the conductive bacterial cellulose membrane is the highest. When the feed ratio of glucosamine to glucose is 100:0, the tensile strength of the amino bacterial cellulose membrane decreases significantly. Figure 7 The infrared chromatograms of amino-modified bacterial cellulose membranes and their modification process are shown (a is amino-modified bacterial cellulose membrane; b is initiator Br-modified bacterial cellulose membrane; c is polymer brush-modified bacterial cellulose membrane; d is bacterial cellulose membrane after copper coating). The results show that after grafting the initiator, the -1 The infrared characteristic peak of initiator Br appears at 1650cm -1 and 3350cm -1 The infrared characteristic peak of the amide bond appears at the surface, indicating that the monomer METAC is successfully polymerized and grafted on the surface of the bacterial cellulose membrane; after the copper plating layer is constructed, the infrared characteristic peak of the above group disappears, further indicating the successful construction of the copper plating layers on the side and front sides.

[0108] Example 4

[0109] In the following embodiments, the amino bacterial cellulose membrane synthesized by biological in situ copolymerization is used as the base material, and the conductive bacterial cellulose is synthesized by polymer-assisted metal deposition technology, and its preparation method is as follows:

[0110] (1) Preparation of 50% amino bacterial cellulose:

[0111] Glucosamine was used as a functional carbon source and added to HS culture medium at a ratio of 1:1 together with glucose carbon source. The two were cultured at 30°C for 5 days through a microbial catalytic biosynthetic metabolic pathway to directly biopolymerize into amino-modified bacterial cellulose with the same amine group density. The amino bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2-4 hours, it was taken out and rinsed with deionized water until neutral. The amino bacterial cellulose membrane was obtained after freeze-drying.

[0112] (2) The initiator is fixed on the surface of amino bacterial cellulose:

[0113] See Example 1

[0114] (3) Introduction of surface polymer brushes:

[0115] Place the bacterial cellulose substrate with the fixed initiator in a Shrek bottle, and add 292.8 mg of bipyridine, 12 mL of methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, 12 mL of methanol (MEOH), 66 mg of cuprous chloride (CuCl) and 43.2 mg of copper bromide (CuBr2) to the bottle in sequence. Immerse the Shrek bottle in a 25-30°C water bath and pass N2 protection for 3-5 minutes, and stir magnetically until the monomer is completely dissolved. After reacting for 2 hours, take out the material, wash it with deionized water several times, freeze-dry it, and store it in a desiccator.

[0116] (4) Growth of Cu conductive coating:

[0117] See Example 1

[0118] like Figure 8 The following are scanning electron microscope images of the conductive bacterial cellulose prepared in Example 4, where a is an amino-modified bacterial cellulose film, b is a film grafted with a grafting initiator Br, c is a polymer-grafted modified film, and d is a bacterial cellulose film after surface copper plating. The results show that with the construction of the copper plating layer on the fiber membrane surface, the surface roughness of the membrane increases significantly, and the formation of a nano-copper particle coating on the membrane surface is clearly observed after comparison. Fig. 9 This is a photo of an application case in which the conductive bacterial cellulose film and polytetrafluoroethylene film obtained in Example 4 are combined to form a friction nanogenerator to power small devices such as LEDs and stopwatches.

[0119] Example 5

[0120] In the following embodiments, the amino bacterial cellulose membrane synthesized by biological in situ copolymerization is used as the base material, and the conductive bacterial cellulose is synthesized by polymer-assisted metal deposition technology, and its preparation method is as follows:

[0121] (1) Preparation of 50% amino bacterial cellulose:

[0122] Glucosamine was used as a functional carbon source and added to HS culture medium together with glucose carbon source in a ratio of 1:1. The two were directly biopolymerized into amino-modified bacterial cellulose through microbial catalytic biosynthesis metabolic pathway and cultured at 30°C for 5 days. The amino-modified bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2-4 hours, it was taken out and rinsed with deionized water until neutral. The amino-modified bacterial cellulose membrane was obtained after freeze-drying.

[0123] (2) The initiator is fixed on the surface of amino bacterial cellulose:

[0124] See Example 1

[0125] (3) Introduction of surface polymer brushes:

[0126] The bacterial cellulose substrate with fixed initiator was placed in a Shrek bottle, and 292.8 mg of bipyridine, 12 mL of methacryloyloxyethyl trimethyl ammonium chloride (METAC) monomer, 12 mL of methanol (MEOH), 66 mg of cuprous chloride (CuCl) and 43.2 mg of copper bromide (CuBr2) were added to the bottle in sequence. The Shrek bottle was immersed in a 25-degree Celsius water bath and passed through N2 protection for 5 minutes, and magnetically stirred until the monomer was completely dissolved. After reacting for 4 hours, the material was taken out and washed with clean water several times, and freeze-dried and freeze-dried, and stored in a desiccator.

[0127] (4) Growth of Cu conductive coating:

[0128] See Example 1

[0129] (5) Biodegradability test

[0130] The amino bacterial cellulose membrane obtained in Example 1 and the conductive bacterial cellulose membrane obtained in Example 5 were placed in a PBS solution at pH 5.0, and 1% cellulase was added to observe their degradation. The glucose concentration in the solution was tested every hour.

[0131] The degradation test results of Example 5 are as follows Fig.10 As shown, the top is a photo of the biodegradation of the amine-modified bacterial cellulose-based film, and the bottom is a photo of the biodegradation of the prepared conductive bacterial cellulose film. The results show that the amine-modified film can be degraded within 4 hours, and the conductive bacterial cellulose film can be completely degraded within 6 hours, and the final degradation product is glucose.

[0132] The conductive bacterial cellulose film provided by the present invention meets the flexibility requirements of the intelligent wearable sensor device and the environmentally friendly requirements of complete biodegradability.

[0133] The present invention provides a method for preparing a conductive bacterial cellulose film and its application. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the concept of the present application, they can also make several simple deductions or substitutions, which should be regarded as belonging to the protection scope of the present application.

Claims

1. A bacterial cellulose-based conductive flexible material, characterized in that: It is a bacterial cellulose membrane with a metal coating on its surface.

2. The bacterial cellulose-based conductive flexible material according to claim 1, characterized in that: The metals include copper, nickel, gold and silver.

3. The method for preparing the bacterial cellulose-based conductive flexible material according to claim 1, characterized in that: The steps include: S1, fixing the initiator on the surface of bacterial cellulose; S2, introducing polymer brushes on the surface of bacterial cellulose membranes via atom transfer radical polymerization; S3. Polymer-assisted metal deposition technology on the surface of bacterial cellulose membrane mediates the growth of metal conductive coating.

4. The method for preparing bacterial cellulose-based conductive flexible material according to claim 3, characterized in that: In step S1, the initiator is a Br-containing initiator. The bacterial cellulose membrane is immersed in a solution of the Br-containing initiator for reaction. After the reaction is completed, the membrane is taken out, cleaned, and freeze-dried in a vacuum to obtain a bacterial cellulose membrane with the initiator fixed on the surface.

5. The method for preparing bacterial cellulose-based conductive flexible material according to claim 3, characterized in that: In step S2, the bacterial cellulose membrane with the initiator fixed on the surface is immersed in a solution containing the monomer methacryloyloxyethyltrimethylammonium chloride for reaction. After the reaction is completed, the membrane is taken out and repeatedly washed with deionized water, and freeze-dried in a vacuum to obtain a polymer brush containing functional groups that can pair with opposite ions on the surface - a bacterial cellulose membrane modified with polymethacryloyloxyethyltrimethylammonium chloride.

6. The method for preparing bacterial cellulose-based conductive flexible material according to claim 3, characterized in that: In step S3, the bacterial cellulose membrane modified by the surface polymer brush is immersed in an active ion solution of electroless deposition to carry out ion exchange and pairing reaction, and then the paired bacterial cellulose membrane is placed in a metal layer plating bath reaction solution for static deposition, taken out and repeatedly washed with deionized water, and finally freeze-vacuum dried to obtain a conductive bacterial cellulose membrane.

7. The method for preparing bacterial cellulose-based conductive flexible material according to claim 4, characterized in that: The initiator solution in S1 is a uniformly mixed solution of dichloromethane, triethylamine, and 2-bromoisobutyryl bromide in a volume ratio of 100~50:0.5~5:0.5~2.

8. The method for preparing bacterial cellulose-based conductive flexible material according to claim 5, characterized in that: The solution containing the monomer methacryloyloxyethyltrimethylammonium chloride is a uniformly mixed solution prepared by configuring bipyridine, methacryloyloxyethyltrimethylammonium chloride monomer, methanol, cuprous chloride and cupric bromide in a molar ratio of 20~1: 5000~100: 4000~100: 10~1: 10~0.

1.

9. The method for preparing bacterial cellulose-based conductive flexible material according to claim 6, characterized in that: In S3, the active ion solution for electroless deposition is a (NH4)2PdCl4 solution with a molar concentration of 0.01-0.1 mM, and the reaction time is 15-120 min.

10. Use of the bacterial cellulose-based conductive flexible material according to claim 1 or 2 in the preparation of an intelligent wearable sensor device.

Citation Information

Patent Citations

  • Conductive textile and its making method

    CN102995395A

  • Antimicrobial bacterial cellulose, preparation method and application thereof

    CN104892842A

  • Electrically conductive textile element and method of producing same

    CN107614783A

  • ATRP modification-based functional bacterial cellulose preparation method

    CN109776732A

  • Copper / silver-based electrode taking conductive bacterial cellulose composite film as substrate

    CN112194818A